Energy-environmental and cost assessment of a set of strategies for retrofitting a public building toward nearly zero-energy building target. (July 2017) - Ferrari, Simone; Beccali, Marco
Highlights: A study on how the energy performance of a tower office building can be improved toward Nearly Zero-Energy Building (nZEB) requirements is presented. Primary energy demand and associated emissions can be reduced up to 40% from the current values. Useful hints to better understand the viability of many commonly adopted retrofitting strategies are provided. Abstract: The purpose of this study was to assess an energy retrofit of a building representative of those in public tertiary stock, to improve energy performance toward nearly Zero-Energy Building (nZEB) requirements. The building is located in the campus of the Politecnico di Milano University (Italy). Several hypothetical improvements regarding the building envelope and plants were assessed in terms of energy savings, costs, and the reduction of greenhouse gas emissions. The results of the study show that it is possible to reduce primary energy demand and associated emissions up to 40% from the current values by adopting market-available and well-proven technological solutions for retrofit. Moreover, exploiting on-site renewable energy sources, the net energy consumption can be near zero. However, an economic analysis of the application of these technologies has highlighted many critical elements related to the implementation of some solutions. This is particularly true for actions related to the thermal insulation of the building envelope and to the installation of ventilation system with heat recovery. Since nZEB requirements are related to the concept of economic performance, this paper gives useful hints to better understand the viability of many commonly adopted actions and strategies for reaching such targets in building retrofit cases.